Pelvimetria radiográfica em diferentes raças de fêmeas caninas adultas (Canis familiaris-LINNAEUS, 1758) - Páfaro, Vanessa [UNESP] (Universidade Estadual Paulista (Unesp), 2007)
As medidas dos diametros da pelve, obtidas diretamente sobre o filme radiografico, sao conhecidas como pelvimetria radiografica. Essa tecnica, que possibilita determinar o padrao pelvimetrico para cada raca, serve como subsidio para metodos profilaticos contra complicacoes que possam ocorrer durante o parto, alem de permitir a classificacao anatomica e obstetrica da pelve. Por meio da pelvimetria foram analisadas radiografias da pelve, na projecao ventrodorsal, de 250 femeas caninas adultas de diferentes racas, a fim de estabelecer as dimensoes pelvicas. Medias e desvios-padrao foram, respectivamente...

The measurements of the diameters of the pelvis, the study radiographic is acquaintance as a pelvimetry radiographic. That know-how makes the assignation by possible standard pelvimetric for each breed , serving as a dole about to prevention against complications than is to may be become of during the break, besides from provide categorization anatomic and obstetric from the pelvis. By pelvimetry have been evaluated radiography the pelvis at the ventrodorsal radiographs of 250 female canine adult of different breeds, for the purpose of establish the dimensions pelvics. The averages and deflections norm have been respectively: Breed Brasilian Mastif... (Complete abstract, click electronic access below)
Keywords: Radiologia; Pelvimetria; Pelve; Fêmeas caninas; Radiology; Pelvimetry; Pelvic; Female canine